The Potential of Islamic Archeology of Talang Pangeran Village as a Source of Local Historical Collection of Ogan Komering Ilir Regency - Pebianti, Sela; Idris, Muhamad; Wandiyo, Wandiyo (Journal of Social Work and Science Education, 2023)
Indonesia will be very rich in relics from ancient times, one of them located in the village of Talang Pangeran where the village has a lot of relics the relic buried in it is one of the relics found in the village gutter princes are ancient tombs, tomboh houses, their buildings, as well the knick-knacks contained in the building that characterize the building. The purpose of this study is to determine the potential of Archeology. What Islam is in the village of Talang Pangeran and will be used later as a source of learning local history. In this study the author uses a qualitative descriptive method which starts from observation activities, interviews, documentation, literature study. In the village of Talang Pangeran has a very rich historical heritage and that all needs to be preserved and developed so that it is lost in time. Therefore researchers are trying as much as possible to preserve it again and can be useful for the researcher and the village community Talang Pangeran.